Study of group education interventions for people with low back pain - Gupta, Rishabh; Mahajan, Shavi; Dewan, Deepika; Gupta, Rajat (International Journal Of Community Medicine And Public Health, 2017)
Background: Backcare education administered in a group situation is one of the most effective and economic methods of treating back pain. It is based on available scientific knowledge of the physiology and mechanics of the spinal structures and their relationship to daily activities. It provides the patient with a better understanding of the problem, aiming primarily at helping the patient take responsibility for his or her back pain, while relieving pain and functional disability. Methods: This study was carried out on 100 patients of chronic low back pain, attending the OPD of Post Graduate Department of Orthopaedics, Government Medical College Jammu for a period of one year. Assessment was carried out before the treatment and after the treatment at four weeks, three months & six months post treatment. The following scales were used to measure the therapeutic response: the Modified Oswestry low back pain disability index, Visual analogue score (VAS), and clinical parameters like finger to floor distance and straight leg raising. Results: The patients showed significant improvement at 1 month, 3 months and 6 months post treatment when compared to base-line data (p<0.001). Conclusions: It was concluded that all chronic low back pain patients would benefit from a group program of back care education.